Diagnostic accuracy of dual-energy CT to determine urinary tract stone composition: Differentiating between uric acid and non-uric acid urinary tract stone - Rojanavijitkul, Pawanaporn; Tantigate, Pattama; Ratchanon, Supoj; Usawachintachit, Manint; Pongpirul, Krit; Chaopathomkul, Bundit (Chulalongkorn Medical Journal, 2022)
Background: The urinary tract stone is a worldwide condition with various clinical significances. Optimal treatment requires multiple considerations including stone composition. Dual-energy computed tomography (DECT) has been used to determine uric acid and non-uric acid urinary tract stones. Objective: To evaluate the diagnostic accuracy of rapid-kilovoltage (kV) switching DECT in differentiating between uric acid and non-uric acid stones compared with reference standard infrared spectroscopy (IRS). Methods: A prospective study enrolled patients from February 2018 to March 2020 who underwent a DECT scan for urinary tract stone with 3-mm stone (s). Post-processed material-density (MD) images were used to differentiate between uric acid and non-uric acid stones. Exclusion criteria included those with no available IRS result or those with an unclear location of the extracted stone on CT images. Diagnostic accuracy was analyzed using SPSS® v.22. Results: A total of 28 patients with 35 urinary tract stones were included composing of 2 uric acid and 33 non-uric acid stones. There were 50.0% sensitivity, 96.8% specificity, 50.0% positive predictive value (PPV), 96.8% negative predictive value (NPV) and 93.9% accuracy of MD images compared to IRS. Conclusion: Rapid-kV switching DECT has high accuracy to determine non-uric acid stones.